2021
DOI: 10.3892/etm.2021.9868
|View full text |Cite
|
Sign up to set email alerts
|

Lidocaine suppresses the malignant behavior of gastric cancer cells via the c‑Met/c‑Src pathway

Abstract: The present study was designed to investigate the role and mechanism of action behind the action of lidocaine in gastric cancer cells. Lidocaine was tested for its potential role in affecting the viability of cells using Cell Counting Kit-8 (CCK-8) assays. It was found that there was a decreased MKN45 cell viability upon lidocaine treatment in a dose-dependent manner. Phosphorylated c-Met, phosphorylated c-Src, c-Met and c-Src levels were detected using western blotting following lidocaine or hepatocyte growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…A recent study demonstrated that lidocaine can reduce the mobility of cancer cells and enhance their sensitivity to drug treatment by inhibiting the MET pathway ( 35 ). Given the increased activation of the MET pathway observed in TMZ-resistant GBM cells, it was reasoned that if lidocaine can inhibit the MET pathway, it may potentially suppress the malignant behavior of GBM cells and enhance the therapeutic effect of TMZ.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study demonstrated that lidocaine can reduce the mobility of cancer cells and enhance their sensitivity to drug treatment by inhibiting the MET pathway ( 35 ). Given the increased activation of the MET pathway observed in TMZ-resistant GBM cells, it was reasoned that if lidocaine can inhibit the MET pathway, it may potentially suppress the malignant behavior of GBM cells and enhance the therapeutic effect of TMZ.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study, lidocaine was revealed to reduce the malignant behavior of gastric cancer cells by inhibiting the c-Met pathway ( 35 ). However, the effect of lidocaine on the HGF/MET pathway in GBM cells remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 42 Lidocaine also enhanced the in vitro effect of 5-fluorouracil in a study examining gastric cancer cells, an effect that may be associated with lidocaine-related inhibition of the c-mesenchymal-epithelial transition factor (c-Met)/Proto-oncogene tyrosine-protein kinase Src (c-Src) pathways leading to decreased B-cell lymphoma 2 (Bcl-2) levels and increased levels of Bax and cleaved caspase-3, resulting in apoptosis. 43 …”
Section: Discussionmentioning
confidence: 99%
“…There are several mechanisms suggested by which lidocaine can induce apoptosis in mammalian cells [102][103][104][105]. However, similarly to studying the effects of lidocaine in HNSCCs, its mechanism(s) of inducing apoptosis following T2R14 activation is/are completely unknown.…”
Section: Lidocaine May Inhibit the Proteasome As A Mechanism Of Apopt...mentioning
confidence: 99%